Analisis Algoritma Analytic Network Process (ANP) Dalam Pemilihan Material Furniture Pada Interior Rumah Tinggal - Fadilla Anissa; Agus Perdana Windarto; M Fauzan (Kesatria : Jurnal Penerapan Sistem Informasi (Komputer dan Manajemen), 2020)
The purpose of this research is to recommend furniture materials in the interior of a residential house. In this study, the authors used a decision support system technique using the Analytic Network Process (ANP) algorithm. The research data source is by conducting interviews and giving questionnaires to furniture users in Pematangsiantar City. In the selection of furniture materials, the author uses five assessment criteria, among others: Quality (C1), Design (C2), Price (C3), Material Maintenance (C4), Room Arrangement (C5). In this study, the alternatives used as samples are Solid Wood (A1), Particle Wood (A2), Plywood Wood (A3), MDF Wood (A4), and Teakblock Wood (A5). From the study results using the Analytic Network Process (ANP) technique, it was found that from the five alternatives selected, obtained A1 became the best recommendation with a value of 0.12. It is hoped that this research can provide input to the public, especially in Pematangsiantar City, in choosing furniture materials to create a comfortable and ideal residence